2016
DOI: 10.1007/s10877-016-9960-3
|View full text |Cite
|
Sign up to set email alerts
|

Early differential diagnosis of the severity of acute pancreatitis

Abstract: There is a great need for early verification of the severity of acute pancreatitis (AP). The early stage of pathogenesis of AP is characterized by endothelial dysfunction which could be determined by wavelet analysis of skin temperature (WAST) technique. The aim is to investigate whether the dysregulation of microvascular tone caused by endothelial dysfunction and detected by WAST can be a significant indicator in early differential diagnosis of AP severity. The WAST performed in the frequency range of 0.0095-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The production of inflammatory mediators in the systemic circulation induces global endothelial dysfunction and increases vascular permeability. Popov et al 19 cold test, and the degree of endothelial dysfunction was correlated with the severity of the disease. Oxygen saturation at admission is an indirect indication of PaO 2 (arterial oxygen pressure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of inflammatory mediators in the systemic circulation induces global endothelial dysfunction and increases vascular permeability. Popov et al 19 cold test, and the degree of endothelial dysfunction was correlated with the severity of the disease. Oxygen saturation at admission is an indirect indication of PaO 2 (arterial oxygen pressure).…”
Section: Discussionmentioning
confidence: 99%
“…The production of inflammatory mediators in the systemic circulation induces global endothelial dysfunction and increases vascular permeability. Popov et al 19 demonstrated the impairment of microvascular function in patients with severe acute pancreatitis by measuring cutaneous temperature changes in response to a cold test, and the degree of endothelial dysfunction was correlated with the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In invertebrates, whether or not there are comparable age‐dependent changes in both aorta and aortic valve functions as in humans (Reinöhl et al, ) is not precisely addressed. However, the two important and opposing functions of vasculature—vasoconstriction and vasodilatation—are directly or indirectly dependent on the properties of the endothelium (Popov, Ershova, Podtaev, Frick, & Zubareva, ).…”
Section: Introductionmentioning
confidence: 99%